Understanding the Catholic Church’s Behavior Under the Dictatorships of Argentina, Chile, and Brazil: Rethinking the Religious Economy Explanation - Ishama Medilien; Timothy John Steigenga (Religions)
During the 1970s’ military dictatorships in Chile and Brazil, the Catholic Church took the position of moral opposition to the authoritarian regimes, while in Argentina, the Church sided with the dictatorship. In his pathbreaking book utilizing the religious economy model, Anthony Gill theorized that the Church in Chile adopted a critical stance against the regime due to competition from Protestant Churches. Subsequently, Gill’s specific arguments and the religious economy model in general have been widely applied but also critiqued by sociologists of religion. Through a deeper analysis of the three case studies of Argentina, Chile, and Brazil, we support and extend theoretical critiques of the religious economy model. We argue that that the religious economy model as applied by Gill is an insufficient predictor of church and state behavior because it lacks specificity on the amount of competition necessary to warrant taking progressive action, lacks specificity about the timing of Protestant competition, ignores the pre-existing position of the Catholic Church, treats the demand side of the religious market as inelastic, assumes the Catholic Church intentionally implemented progressive policies in response to competition, presumes the Church is a unitary actor, and disregards the impact of a perceived Marxist threat on both church and state actors. Our critique of the religious economy model points to refinements of the model and alternative approaches to understanding church and state behavior in Latin America and elsewhere.